2015
DOI: 10.2147/ceg.s86419
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity, specificity, predictive values, and likelihood ratios of fecal occult blood test for the detection of colorectal cancer in hospital settings

Abstract: ObjectivesTo study the performance of a single test using two fecal occult blood tests with colonoscopy for the detection of colorectal cancer (CRC) for the first time in Saudi Arabia to determine possible implications for the anticipated colorectal screening program.Materials and methodsWe compared the performance of guaiac and immunochemical fecal occult blood tests for the detection of CRC among patients of 50–74 years old attending two hospitals in the Eastern Region of Saudi Arabia. Samples of feces were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…Urine dipstick in an emergency room screening setting for detecting diabetic ketoacidosis yields a PPV = 0.15 but NPV = 0.99. G-FOBT provides a PPV = 0.35 and NPV = 0.99 for detecting colorectal cancer [34] . Low-dose computed tomography for lung-cancer screening provides a PPV = 0.42 and NPV = 0.99.…”
Section: Discussionmentioning
confidence: 99%
“…Urine dipstick in an emergency room screening setting for detecting diabetic ketoacidosis yields a PPV = 0.15 but NPV = 0.99. G-FOBT provides a PPV = 0.35 and NPV = 0.99 for detecting colorectal cancer [34] . Low-dose computed tomography for lung-cancer screening provides a PPV = 0.42 and NPV = 0.99.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a wide variety of biomarkers available [ 37 , 38 , 39 ], detection of cancer often requires the use of several biomarkers in tandem to provide a molecular signature sufficiently robust enough to accurately indicate the presence of cancer [ 33 , 40 , 41 ]. More than 50% of all human proteins are glycosylated [ 42 ] and glycosylation is one of the most complex and common post-translational modifications.…”
Section: Cancer and The Glycomementioning
confidence: 99%
“…False positives are common due to usage of mediations such as nonsteroidal anti-inflammatory drugs as well as dietary intake of red meat [ 16 , 17 ]. A single FOBT has a sensitivity of only around 50% [ 18 , 19 ], and while repeated testing can boost sensitivity, patients may be less willing to attend multiple appointments [ 20 ]. The fecal immunochemical test (FIT) is an antibody-based measurement of hemoglobin protein in stool.…”
Section: Introductionmentioning
confidence: 99%
“…The fecal immunochemical test (FIT) is an antibody-based measurement of hemoglobin protein in stool. One study found that the FOBT provided a specificity of only 78% while the FIT offered a specificity of over 90% [ 19 ]. The FIT also has a higher average sensitivity for CRC of 93%, but has only a 48% sensitivity for advanced neoplasia, suggesting that it may not be optimal for identifying individuals at risk for CRC [ 21 ].…”
Section: Introductionmentioning
confidence: 99%